Oxyspirura petrowi Causing Ocular Parasitism in a Free-Ranging Common Buzzard (Buteo buteo) in Romania and a Review of the Potential Zoonotic Implications as Cutaneous Larval Migrans - Călin Mircea Gherman; Angela Monica Ionică; Katarzyna Anna Hołówka; Vlad Dan Cotuțiu; Carla Andreea Culda; Georgiana Iulia Lupu; Andrei Daniel Mihalca (Animals)
Bird eyes are more neglected organs in studies targeting the structure of the helminth fauna, which are instead mainly focused on the digestive and respiratory systems. In an extended study aimed at identifying helminths in the common buzzard (Buteo buteo), the eyes of 92 birds were also examined. Morphological characteristics and molecular analyses were used to identify the collected specimens. Eyeworms were found in only one bird, a juvenile male (1/92; 1.08%). Two nematodes were collected, a female and a fourth-stage larva. This is the first report of Oxyspirura petrowi in the common buzzard. The results highlight the need for careful examination of raptors’ eyes as ocular parasitism can affect their vision.